1982
DOI: 10.1515/zna-1982-0316
|View full text |Cite
|
Sign up to set email alerts
|

The Response of CO2 Evolution from Soils to Global Temperature Changes

Abstract: Own experiments and literature data point at a strong correlation between mineralization processes in soils i.e. the corresponding CO2 release and temperature variations. This seems to be important with regard to the global CO2 problem, since it implies that due to the global temperature increase over 80 years large additional amounts of CO2 were released to the atmosphere. These additional quantities seem to have been at least as important as the anthropogenic release of CO2 from the burning of fossil fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 13 publications
12
50
0
Order By: Relevance
“…Although it is believed that soil carbon emission may be enhanced by the global warming for its temperature effect (Billings et al, 1982;Schleser, 1982;Raich and Schlesinger, 1992;Kirschbaum, 1995), it is possible that the presumed enhancement of soil respiration may be offset by the soil moisture effect as shown in our results. The overall effect can only be adequately evaluated by treating the temperature sensitivity measure as a function of, at least, temperature and moisture.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although it is believed that soil carbon emission may be enhanced by the global warming for its temperature effect (Billings et al, 1982;Schleser, 1982;Raich and Schlesinger, 1992;Kirschbaum, 1995), it is possible that the presumed enhancement of soil respiration may be offset by the soil moisture effect as shown in our results. The overall effect can only be adequately evaluated by treating the temperature sensitivity measure as a function of, at least, temperature and moisture.…”
Section: Discussionmentioning
confidence: 63%
“…Numerous studies have sought to establish a relationship of soil respiration rate with soil moisture and temperature (e.g. Schleser, 1982;Lloyd and Taylor, 1994;Thierron and Laudelout, 1996;Davidson et al, 1998;Gulledge and Schimel, 2000;Xu and Qi, 2001a). However, up to date it is still unclear how Q 10 is affected by factors other than temperature (Carlyle and Than, 1988;Simmons et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…T opt was ®xed at 258C and Q 10 at 2.2 (Cou Ãteaux et al, 2001). The assumption of a constant value of Q 10 could be questionable because it has been shown that Q 10 decreases with temperature (Schleser, 1982;Kirschbaum, 1995; Dalias et al, 2001a,b). Nevertheless, Cou Ãteaux et al (in press) comparing the validity of the response function to temperature using a ®xed Q 10 and a mobile Q 10 , related to daily temperature and based on published data, did not ®nd any improvement in the explanatory value of the response function and suggested that the simplest procedure should be used for calculation.…”
Section: Decomposition Response Function To Climatementioning
confidence: 99%
“…Many studies have shown that soil C mineralisation increases exponentially with increasing temperature (e.g. Schleser, 1982) and a positive feedback is expected between the liberation of soil carbon and the temperature rise. The potential net transfer of CO 2 to the atmosphere depends on the imbalance between the rates of decomposition and net primary production.…”
Section: Introductionmentioning
confidence: 99%
“…That could generate a positive feedback to global warming, because CO 2 is an important greenhouse gas [15][16][17]. The likelihood that this particular feedback will emerge has been extensively discussed [18][19][20][21][22][23] but has not been ruled out [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%